E-Learning as A Learning Media Innovation Islamic Education - Hoerudin, Cecep Wahyu; Syafruddin, Syafruddin; Mayasari, Annisa; Arifudin, Opan; Lestari, Sisca (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The use of technology in the digital era is an alternative way to maximize learning for students, especially distance learning. E-learning is a new model of learning in the digital era. This research aims to determine the extent of implementing e-learning based learning in Islamic religious education lessons in SKI learning at MAN Purwakarta. This type of research is a type of qualitative research with descriptive methods. The results of this research show that there are three functions of E-Learning as a learning medium: Additional Function, Complementary Function, and Substitute Function. Then, in the Islamic religious education learning process, the use of e-learning has three stages, namely the planning, implementation, and evaluation stages. The existence of E-learning makes it easier and faster to convey Islamic religious lessons even though there are still shortcomings. Human efforts to adapt to a learning system that continues to change is a concrete step in building an adaptive generation in every era.